In-line phase contrast imaging of hepatic portal vein embolization with radiolucent embolic agents in mice: a preliminary study. - Rongbiao Tang; Wei Huang; Fuhua Yan; Yong Lu; Wei-Min Chai; Guo-Yuan Yang; Ke-Min Chen (PLoS ONE, 2013)
It is crucial to understand the distribution of embolic agents inside target liver during and after the hepatic portal vein embolization (PVE) procedure. For a long time, the problem has not been well solved due to the radiolucency of embolic agents and the resolution limitation of conventional radiography. In this study, we first reported use of fluorescent carboxyl microspheres (FCM) as radiolucent embolic agents for embolizing hepatic portal veins. The fluorescent characteristic of FCM could help to determine their approximate location easily. Additionally, the microspheres were found to be fairly good embolizing agents for PVE. After the livers were excised and fixed, they were imaged by in-line phase contrast imaging (PCI), which greatly improved the detection of the radiolucent embolic agents as compared to absorption contrast imaging (ACI). The preliminary study has for the first time shown that PCI has great potential in the pre-clinical investigation of PVE with radiolucent embolic agents.